2013
DOI: 10.1103/physrevd.87.084014
|View full text |Cite
|
Sign up to set email alerts
|

BTZ black holes inspired by noncommutative geometry

Abstract: In this paper a Banados, Teitelboim and Zanelli (BTZ) black hole is constructed from an exact solution of the Einstein field equations in a (2+1)-dimensional anti-de Sitter spacetime in the context of noncommutative geometry. The BTZ black hole turns out to have two horizons, no horizon or a single horizon corresponding to a minimal mass. Certain thermodynamical properties are investigated, including Hawking temperature, entropy and heat capacity. Also discussed is the geodesic structure of BTZ black holes for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…Recently Rahaman et al [65] have found a BTZ black hole inspired by noncommutative geometry with negative cosmological constant Λ. The metric is given by…”
Section: Construction Of Thin-shell Wormholementioning
confidence: 99%
See 1 more Smart Citation
“…Recently Rahaman et al [65] have found a BTZ black hole inspired by noncommutative geometry with negative cosmological constant Λ. The metric is given by…”
Section: Construction Of Thin-shell Wormholementioning
confidence: 99%
“…A number of studies on the exact wormhole solutions in the context of noncommutative geometry can be found in the literature [60][61][62][63][64]. Recently, Rahaman et al [65] have investigates the properties of a BTZ black hole [66] constructed from the exact solution of the Einstein field equations in a (2 + 1)-dimensional anti-de Sitter space-time in the context of noncommutative geometry. They showed that noncommutative geometry background is able to account for producing stable circular orbits, as well as attractive gravity, without any need for exotic dark matter.…”
Section: Introductionmentioning
confidence: 99%
“…By solving the Einstein equations with an EOS p r = −ρ, as a matter source, we have the following relationship (see Ref. [2]):…”
Section: Interior Geometrymentioning
confidence: 99%
“…From the fundamental point of view of noncommutative geometry there is an interesting interplay between mathematics, high energy physics as well as cosmology and astrophysics. In a noncommutative spacetime the coordinate operators on a D-brane [20,21] can be encoded by the commutator [x μ ,x ν ] = iϑ μν , wherex and iϑ μν are the coordinate operators and an antisymmetric tensor of dimension (length) 2 , which determines the fundamental cell discretization of spacetime. As Smailagic et al have shown [22] that noncommutativity replaces point-like structures by smeared objects in flat spacetime.…”
Section: Introductionmentioning
confidence: 99%
“…Making use of Finch and Skea [8] ansatz in (2 + 1) dimensions, Banerjee et al [9] have generated new class of physically acceptable interior solutions corresponding to the BTZ exterior. Rahaman et al [10] have studied the properties of BTZ black hole by proposing new exact solutions of Einstein's field equations in (2 + 1) dimensional anti-de Sitter back ground space-time in the context of non-commutative geometry.…”
Section: Introductionmentioning
confidence: 99%